(untitled) (Seminar_BG, 2025)
The article introduces the concept of urban fallows as specific intermediate territories within contemporary city, which combine cultural, social, and ecological density, despite their apparent abandonment. The term fallows is derived as a metaphor borrowed from agriculture, which acquires a new meaning in an urban context: a temporary retreat from capital-centric productivity, which makes possible the emergence of alternative social and ecological processes. The text analyzes fallow lands as territories of imagination, oblivion, examining how memory and potential, nature and culture, as well as civic participation and institutional inaction, intertwine in them. The analysis combines a theoretical discussion of contemporary urban, cultural, and philosophical perspectives with empirical observations and field-based research. A central case study focuses on the area surrounding Stochna Gara in Sofia, examined through the research and practice of the multidisciplinary collective GRADOSCOPE, of which the author is a member. Situated within broader European tendencies toward temporary use and cultural reactivation of disused sites, the case serves as a basis for critically reflecting on the possibilities and limitations of integrating urban fallows into long-term, resilient urban strategies. References Amin, A. & Thrift, N. J. (2002). Cities: Reimagining the Urban. Cambridge: Polity. ‌Bhabha, H. K. (1994). The Location of Culture. London: Routledge. Clément, G. (2010). Manifest der dritten Landschaft. Berlin: Merve Verlag. Corboz, A. (1983). The Land as Palimpsest. Diogenes, 31(121), 12–34. Dolezal, S. (2015). Recycling Space. Reframing Urban Derelict Sites and Properties. Exploring Space Theories from Henri Lefebvre to Urban Catalyst [Master’s thesis]. https://www.academia.edu/16561066/Recycling_Space_Reframing_Urban_Derelict_Sites_and_Properties_Exploring_Space_Theories_from_Henri_Lefebvre_to_Urban_Catalyst [15.12.2025] Foucault, J. M. (1986). Of Other Spaces (Miskowiec, J. Trans.). Diacritics, 16(1), 22-27. https://doi.org/10.2307/464648. Gandy, M. (2002). Concrete and Clay Reworking Nature in New York City. Cambridge: MIT Press. Gandy, M. (2022). Natura Urbana: Ecological Constellations in Urban Space. Cambridge: MIT Press. https://doi.org/10.7551/mitpress/10658.001.0001. Haraway, D. (2016). Staying with the Trouble: Making Kin in the Chthulucene. Durham: Duke University Press. Jencks, C. (1993). Heteropolis. Los Angeles: The Riots and the Strange Beauty of Hetero-Architecture. London: Academy Editions. Kowarik, I. (1992). Das Besondere der städtischen Flora und Vegetation. Schriftenreihe des Deutschen Rates für Landespflege 61, „Natur in der Stadt – ein Beitrag der Landespflege zur Stadtentwicklung“, 33–47. https://www.researchgate.net/profile/Ingo-Kowarik/publication/259364097_Das_Besondere_der_stadtischen_Vegetation/links/0deec52b347dc630c6000000/Das-Besondere-der-staedtischen-Vegetation.pdf [15.12.2025] Kozak, W. (2024). How to Uncover and Nurture Potential Hidden in Empty Spaces? Multiplying Perspectives through the Construction of a Counter-Archive 2024. [Master’s thesis] https://www.politesi.polimi.it/handle/10589/217557 [15.12.2025] Lefebvre, H. (1974). The Production of Space. Oxford: Blackwell. Lefebvre, H. (2004). Rhythmanalysis: Space, Time and Everyday Life. London: Continuum. Locke, J. (1690). An Essay concerning Human Understanding. London: Dent. Mariani, M., & Barron, P. (еds.). (2014). Terrain Vague: Interstices at the Edge of the Pale. London: Routledge. Soja, E. W. (1989). Postmodern Geographies: The Reassertion of Space in Critical Social Theory. London: Verso. Solà-Morales, Ig. (1995). Terrain Vague. In C. Davidson (ed.). Anyplace. Cambridge: MIT Press, 118–123. Stanilov, K. (2007). The Post-Socialist City: Urban Form and Space Transformations in Central and Eastern Europe after Socialism. Dordrecht: Springer Verlag. Till, J. (2009). Architecture Depends. Cambridge: MIT Press. Tsing, A. (2015). The Mushroom at the End Of The World: On the Possibility of Life in Capitalist Ruins. Princeton: Princeton University Press. Schnier, D., Ziehl, M., Osswald, S. & Hasemann, O. (еds.). (2012). Second Hand Spaces: Recycling Sites Undergoing Urban Transformation. Über das Recyceln von Orten im städtischen Wandel. Berlin: Jovis Verlag.